Throwing performance and shoulder injury risk in adolescent male water polo players in South Africa: exploring anthropometric and musculoskeletal parameters and evaluating the impact of a four week in-season conditioning program - Mackenzie, Kelly Candice (Department of Human Biology, 2025)
using only one hand to interact with the ball at any given time. Consequently, catching and passing predominantly rely on the dominant arm whilst treading water. Although shoulder injuries are common, limited research exists regarding the specific factors that contribute to both sub-acute and chronic shoulder pain. Additionally, there is a dearth of evidence on the effectiveness of injury prevention interventions; programs designed to decrease the likelihood of injury and enhance performance. This novel research therefore aims to both; identify and understand the relationship between musculoskeletal parameters in adolescent water polo players and throwing performance and to investigate the effectiveness of a conditioning programme on musculoskeletal parameters associated with injury risk and throwing performance in adolescent water polo players. The thesis includes one literature review and two original research papers. The literature review highlights that; shoulder injuries are pervasive in water polo acros